The Cultural Impact of UNSC Resolution 1325: Fictional Representations of Wartime Sexual Violence - Romão, Ana (2023)
The UNSCR 1325, advocating for gender mainstreaming in peacebuilding operations, acknowledged the disproportionately high impact of armed conflicts on women and children. Even though UNSCR 1325 encompassed different ways in which women and children can be affected by war (e.g. displacement, etc.), this article focuses on one of the topics it addresses: sexual violence against women and girls in warzones. Through the analysis of two case studies, the article will provide an overview of depictions of conflict-related sexual violence in mainstream war cinema. It intends to demonstrate how popular fictional representations of sexual violence in warzones have contributed to shape Western societies’ collective perspectives on the subject. The article will explore the progression, and future challenges, of fictional portrayals of wartime sexual violence in order to assess how Western cultural productions have accompanied UNSCR 1325 throughout the two decades of its existence.